2019
DOI: 10.3390/biom10010020
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hepatocellular Carcinoma Progression through FOXM1 and EMT Inhibition via Hydroxygenkwanin-Induced miR-320a Expression

Abstract: Daphne genkwa, a Chinese medicinal herb, is used frequently in Southeast Asian countries to treat diseases; the flavonoid hydroxygenkwanin (HGK) is extracted from its flower buds. The bioactivity of HGK, particularly as an anti-liver cancer agent, has not been explored. In this study, human hepatocellular carcinoma (HCC) cell lines and an animal xenograft model were employed to investigate both the activity of HGK against liver cancer and its cellular signaling mechanisms. HCC cells treated with HGK were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…In addition, reports have shown that miR-320a is often downregulated in an extended spectrum of cancer types including breast, liver, prostate, lung, and glioma, and is associated with patient survival and tumor stage [ 5 – 9 ]. Mechanistically, miR-320a may inhibit FOXM1 expression, thus suppressing FOXM1-induced epithelial-mesenchymal transition and metastasis [ 10 , 11 ]. miR-320a has also been shown to negatively regulate invasion of tumor cells by blocking HMGB1 or STAT signaling [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reports have shown that miR-320a is often downregulated in an extended spectrum of cancer types including breast, liver, prostate, lung, and glioma, and is associated with patient survival and tumor stage [ 5 – 9 ]. Mechanistically, miR-320a may inhibit FOXM1 expression, thus suppressing FOXM1-induced epithelial-mesenchymal transition and metastasis [ 10 , 11 ]. miR-320a has also been shown to negatively regulate invasion of tumor cells by blocking HMGB1 or STAT signaling [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…HGK induced DNA damage, cell cycle arrest, and cell apoptosis in glioma [20]. HGK inhibited cell migration, invasion, and proliferation in oral squamous cell carcinoma and hepatocellular carcinoma [21,22]. These data suggest that HGK is one of the active antitumor flavonoids in the Genkwa Flos extract.…”
Section: Isolation and Identification Of Flavonoids From Genkwa Flosmentioning
confidence: 71%
“… 10 Chou et al asserted that miR-320a could inhibit the expression of the transcription factor FOXM1 and downstream proteins related to EMT, thereby leading to the suppression of liver cancer cell growth and invasion. 24 Zhang et al reported that miR-320a inhibits endometrial carcinoma cell metastatic capability by preventing TGF-β1-induced EMT. 25 Previous studies also reported that BGN could induce the EMT process of diverse malignancies.…”
Section: Discussionmentioning
confidence: 99%